The impact of the SARS-CoV-2 epidemic outbreak on the vascular access team operations after conversion to COVID-19 dedicated hospital. Issue 5 (September 2022) - Deganello, Elisa; Gastaldo, Francesco; Masiero, Sonia; Fasson, Milena; Colopi, Riccardo Ivan; Girotto, Luciano; Monticelli, Jacopo; Marcante, Elena; Furlan, Patrizia; Baldo, Vincenzo; Pilerci, Claudio; Realdon, Piero; et al.
Background: On February 21 2020, in Schiavonia Hospital occurred the first death by COVID-19 in Italy and since this date SARS-CoV-2 caused more than 100, 000 deaths in our country. Our hospital was immediately closed and re-opened after 15 days as a reference Covid Hospital. Among services involved in a process of destruction and rebirth there was also the Vascular Access Team. Methods: We analyzed our Vascular Access Team activity comparing data from the first month (March) in which basically it did not work and data from the following month (April) in which we began to re-build the Team adapting it to the new reality. Results: In all patients admitted to Intensive Care Unit a Centrally Inserted Central Catheter multilumen was placed, but in March only 5.5% of patients admitted to Medicine-Sub-intensive Unit had a catheter different from the short peripheral cannula while in April it was possible to guarantee a more suitable catheter 31.7% of patients admitted to Medicine-Sub-intensive Unit ( p < 0.000). In April, compared to March, a significant higher number of Midline were implanted in Medicine-Sub-intensive Unit (36/139 vs 12/238 p < 0.000) where also a higher number of Centrally Inserted Central Catheter and Femoral Inserted Central Catheter were implanted (8/139 vs 1/238 p = 0.003). This change allowed us to implant more vascular accesses in Medicine-Sub-intensive Unit favoring Midline with a longer average duration. Only one patient with Midline developed a catheter vein thrombosis, and in only one patient the device was removed for suspected infection. Conclusions: The experience we gained will allow us to be more prepared in the future and our experience has highlighted that a structured Vascular Access Team is necessary to respond adequately to COVID-19 patients' needs, to ensure the effectiveness of the maneuver, to reduce complications and to avoid the waste of resources, always working in safe condition.